Caracterização nutricional, antinutricional, bioquímica e atividades biológicas de sementes de Sesbania Virgata (cav.) pers. - Sá , Giulian César da Silva (2017)
Sesbania virgata is a shrub belonging to a family Leguminosae whose fruit presents seeds with high protein content. Considering the potential of use of this species as a biotechnological tool, the objective this paper was to characterize the seeds of S. virgata (Cav.) Pers., as well as evaluate extracts and fractions for a presence of some biological activities of medical and pharmacological interest. For this, S. virgata seeds were collected in the city of João Pessoa, Paraíba, and had their morpho-physical-chemical characteristics determined. Afterwards, the seeds were delipidated, processed and solubilized in extractive solutions, obtaining 30 extracts and 10 protein fractions, allowing a characterization of the antinutritional factors; protein and amino acid profile; and biological activities. The nutritional characteristics of the seed flour emphasize its high protein content. The optimization of the production of extracts and fractions allowed obtaining the total crude extract (EBT), purification of the protein fraction with lectin activity (FPAL) and the determination of several antinutritional factors. The protein analyzes revealed 60.79% of total protein for the fine flour (FF), 49.34% for EBT and 55.84% for FPAL. With molecular weights between 31-225 kDa, FF, EBT and FPAL presented antioxidant activity. However, they did not present antibacterial activity against the strains investigated, but promoted the inhibition of Candida albicans, C. tropicalis, Aspergillus flavus and Penicillium citrinum. In addition to the high protein content and biological activities, it is important to incorporate new analyzes into the products so that, in the future, they will be viable in the food or pharmaceutical industry, by creating of topical drugs to control fungal contamination or reduction of the damage caused to human health by free radicals and other oxidants.